2000
DOI: 10.1046/j.1365-3040.2000.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine increases chilling tolerance and reduces chilling‐induced lipid peroxidation in Zea mays L.

Abstract: Chilling tolerance was increased in suspension‐cultured cells and seedlings of maize (Zea mays L. cv ‘Black Mexican Sweet’) grown in media containing glycinebetaine (GB). A triphenyl tetrazolium chloride (TTC) reduction test indicated that after a 7 d chilling period at 4 °C, cells treated with 1 mm GB at 26 °C for 1 d had a survival rate (30%) that was twice as high as that of untreated controls. The addition of 2·5 m M GB to the culture medium resulted in maximum chilling tolerance (40%). The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 51 publications
4
71
0
Order By: Relevance
“…However, the maximum glycine betaine content was recorded from the treatment with 1.0 μM concentration of EBR under both conditions. In maize, chilling tolerance has been associated with buildup of glycine betaine (Chen et al 2000). The correlation coefficient analysis between cold stress and morpho-physiological and biochemical attributes (Table 5) revealed that growth characters has positive correlation with morpho-physiological and biochemical traits.…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximum glycine betaine content was recorded from the treatment with 1.0 μM concentration of EBR under both conditions. In maize, chilling tolerance has been associated with buildup of glycine betaine (Chen et al 2000). The correlation coefficient analysis between cold stress and morpho-physiological and biochemical attributes (Table 5) revealed that growth characters has positive correlation with morpho-physiological and biochemical traits.…”
Section: Resultsmentioning
confidence: 99%
“…Membranes, and their integral and associated components used for the uptake and distribution of ions and solutes, are considered to be determinants for developing stress-resistant crops. Low concentrations of glycinebetaine can improve salt and cold stress tolerance, possibly by protecting photosynthetic protein complexes (Holmström et al, 2000) and by reducing the lipid peroxidation of cell membranes (Chen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously applied glycinebetaine improves the growth and production of some plants under stress (Naidu et al, 1998;Chen et al, 2000;Hussain et al, 2008). In many crop plants the natural accumulation of glycinebetaine is lower than sufficient to ameliorate the adverse effects of dehydration caused by various environmental stresses (Subbarao et al, 2000).…”
Section: Use Of Osmoprotectantsmentioning
confidence: 99%